Problems of Upgrading Statistic Estimation of Non-Observed Economy in Uzbekistan - B. A. Begalov; I. E. Zhukovskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
The goal of the article is to find key trends in upgrading statistic estimation of non-observed economy in the Republic of Uzbekistan by using international experience, digital technologies, analytical and statistic methods. The principle elements for preparing this publication were official statistic data of the Statistic Agency under the President of the Republic of Uzbekistan, international regulations and methodology on statistic estimation of  non-observed economy. In the research the authors used methods of generalizing results of questionnaire and expert surveys, sample methods of examination, resource method, method of using the data of labour market and some specific methods of data processing based on digital technologies and statistic information systems. The present theoretical provisions were analyzed, methodology of statistic departments of different countries on statistic estimation of non-observed economy was studied and on the basis of this experience statistic research and calculations were carried out in Uzbekistan in order to upgrade methods and practice of statistic estimation of  non-observed economy. Statistic estimation of non-observed economy conducted for the 1st time in Uzbekistan showed that today there is no uniform methodology but serious steps have been taken in this direction: methods are upgraded, new criteria are being worked out, which could foster stock-taking and complex measures aimed at wellbalanced development of industries and fields of economy in the country.